2022
DOI: 10.1177/09504222221121283
|View full text |Cite
|
Sign up to set email alerts
|

Innovative online learning in entrepreneurship education: The impact of embedding real-life industry practice in the virtual learning environment

Abstract: Applied areas of entrepreneurship are growing in popularity due to the ongoing need for students to gain specialised skills to find employment after graduation. This study explores how educational scaffolding can facilitate the delivery of online experiential activities to improve the entrepreneurial learning experience and the performance of music management students by using information and communications technology tools within the virtual learning environment. A case study methodology was adopted to presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Several gathered studies indicate that experiential learning and project-based learning are considered effective in entrepreneurship education. (Bandera et al, 2018;Oliver & Oliver, 2022;Pal'Ová et al, 2020). Bandera et al (2018) found that experiential entrepreneurship education supported by technology has a positive influence on students' inclination to take risks.…”
Section: ) Entrepreneurship Education In Today's Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…Several gathered studies indicate that experiential learning and project-based learning are considered effective in entrepreneurship education. (Bandera et al, 2018;Oliver & Oliver, 2022;Pal'Ová et al, 2020). Bandera et al (2018) found that experiential entrepreneurship education supported by technology has a positive influence on students' inclination to take risks.…”
Section: ) Entrepreneurship Education In Today's Challengesmentioning
confidence: 99%
“…Similarly, research conducted by Pal'Ová et al (2020) indicates that project-based learning supported by technology enhances students' motivation and engagement in the learning process. Furthermore, in a case study conducted by Oliver & Oliver (2022), experiential learning activities were found to enhance the understanding of one's role and responsibilities in a business simulation. Interventions such as online experiential learning activities were introduced to enhance the entrepreneurship learning experience and improve student performance.…”
Section: ) Entrepreneurship Education In Today's Challengesmentioning
confidence: 99%
See 3 more Smart Citations